An extremal problem for the non-overlapping domains - Targonskii, A. (Український математичний вісник, 2017)
Sharp estimates of product of inner radii for pairwise disjoint domains are obtained. In particular, we solve an extremal problem in the case of arbitrary finite number of free poles on the system points on the rays.